THE POTENTIAL OF RIVER IN URBAN SPACES - Tereza Havránková (European Scientific Journal, ESJ, 2014)
This article, "The potential of river in urban space " is the theme about changes embankment zones and rivers. Article is based on author´s scientific research which aimed to the theoretical part and practical part. The origin theoretical part is an outline of possible uses and waterfront concepts, their problems and inspiring examples of solutions. On the basis of information obtained are systematised the basic problems of the waterfront and rivers and principles of their solutions. The paper on the practical part presents the concept of ideological solutions waterfront area at the northern periphery of Prostějov, the river Hloučela. Design concept precedes the analysis of literary sources and evaluation of selected objects waterside areas. The concept design is also based on the results of the analyzes, analyzes and investigations. The principles are identified as working in the design model object. The solution tries to understand and reproduce the natural essence of the river and its landscape and capitalize on potential Hloučela mainly within the natural corridor on the outskirts of town.